Hubungan Tingkat Pendidikan Ibu Dan Pemberian Asi Eksklusif Dengan Kejadian Stunting Pada Balita Di Provinsi Sulawesi Selatan Tahun 2015 - mustamin mustamin; ramlan Asbar; Budiawan Budiawan (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
Stunting is caused by three factors, involving individuals’ food intake, birth weight, and health condition; the quality and quantity of food nutrition, human resources, number and family structure, parenting, health care, and services; and environmental factors that include social infrastructure, educational services and health services.This aimed to find the relationship between mothers’ education level and exclusive breastfeeding toward the toddlers’ stunting in South Sulawesi Province 2015 based on the report of secondary data analysis on Nutrition Status (PSG) 2015.This research used 2015 PSG data with observational design. The samples in this research were toddlers in 3 cities or regency in South Sulawesi Province with the highest stunting event rate, they were Jeneponto (300 toddlers), Pangkep (300 toddlers) and Tana Toraja (298 toddlers). Secondary data were taken from PSG report of 2015. The nutrition status was measured by anthropometry. Mothers’ education level and exclusive breastfeeding data were obtained by asking respondents using PSG 2015 questionnaires. To find out the relationship of two variables, it was conducted yate's correlation test using SPSS program. The data were presented in the form of frequency distribution tables and narration.The results showed that the prevalence of stunting was 44%. The proportion of lower educated mothers was 56.5%, while exclusive breastfeeding was quite high at 94.8%. Mothers with less education (27.7%) had stunting children, while 27.3% well-educated mothers have normal children and there was a significant relationship between mother education level and stunting on toddlers (p = 0,001). The stunting was found on toddlers who are not exclusively breastfed (0.9%) and exclusively breastfed (43.1%), and there was a significant relationship between exclusive breastfeeding and stunting incidence in toddlers (p = 0.000).